The feasibility and effectiveness of using biological products on onions (Allium cepa L.) in an annual crop - I. I. Irkov; O. N. Uspenskaya; N. I. Bernaz (Овощи России, 2024)
Relevanse. Rhizosphere associative bacteria, multiplying on root secretions, provide the plant with the entire complex of necessary nutrients from the soil and help increase productivity.The purpose of the research was to identify the feasibility and effectiveness of using bacterial preparations, optimizing the rates and timing of their application when cultivating onions as an annual crop on alluvial meadow soils of the Non-Chernozem Zone.Materials and Methods. Field experiments were carried out on the experimental field of VNIIO on an area of 1000 m2 in 2021-2023. We used drugs provided by the Federal State Budgetary Scientific Institution "All-Russian Research Institute of Agricultural Microbiology" (St. Petersburg): BisolbiPlant BIS88 (Bacillus pumilis strain); N40 – Experimental strain (Paenibacillus xylanexedens) – bacillary nitrogen fixer; V514 – Experimental strain (Bacillus megaterium) – bacillary stimulator of mobilization of soil phosphates and phosphorus from mineral fertilizers. The following tasks were solved by year: 2021 – Integrated use of biological products at application rates, l/ha: 0.0; 10.0; 20.0; 40.0; 2022 – Application of biological products in the following options: Control, Control + BIS88 (1+1) l/ha, Control + BIS88 (1+1) l/ha + N40 (1+1) l/ha + V514 (1+1) l/ha; 2023 – Options: BIS88 (0.5+0.5) l/ha + N40 (0.5+0.5) l/ha + V514 (0.5+0.5) l/ha at different base levels spring fertilization: N160P160K160; N110P110K110; N60P60K60.Results. It is not advisable to apply the studied bacterial preparations at a total rate of more than 10.0 l/ha during the cultivation of onions due to plant disease with bacteriosis. The use of the BisolbiPlant drug at a rate of (0.5+0.5) l/ha helps to increase the yield of onions with harvest quality comparable to the control. Biological products applied in combination with irrigation water during the growing season: BIS88 (0.5+0.5) l/ha; N40 (0.5+0.5) l/ha; V514 (0.5+0.5) l/ha, provide an increase in yield (13.4%) with harvest quality comparable to the control in the case of a low (N60P60K60) level of basic spring fertilizer application with subsequent fertilizing during the growing season Ca40N30 + N40K40 + N40K40. At the rates of the main spring application of fertilizers N110P110K110 and N160P160K160, complex application of preparations does not ensure an increase in the yield and its quality.